2023
DOI: 10.1038/s41467-023-38184-3
|View full text |Cite
|
Sign up to set email alerts
|

Enabling accurate and early detection of recently emerged SARS-CoV-2 variants of concern in wastewater

Abstract: As clinical testing declines, wastewater monitoring can provide crucial surveillance on the emergence of SARS-CoV-2 variant of concerns (VoCs) in communities. In this paper we present QuaID, a novel bioinformatics tool for VoC detection based on quasi-unique mutations. The benefits of QuaID are three-fold: (i) provides up to 3-week earlier VoC detection, (ii) accurate VoC detection (>95% precision on simulated benchmarks), and (iii) leverages all mutational signatures (including insertions & deletions).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…A time-dependent and accurate reference barcode for circulating VoCs are often required to identify emerging variants 34,35 . Therefore, these methods (such as Freyja and COJAC) are potentially restricted from identifying or forecasting potential novel variants in the absence of clinical sequencing data and require a "correct" barcode of circulating VoCs for accurate detection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A time-dependent and accurate reference barcode for circulating VoCs are often required to identify emerging variants 34,35 . Therefore, these methods (such as Freyja and COJAC) are potentially restricted from identifying or forecasting potential novel variants in the absence of clinical sequencing data and require a "correct" barcode of circulating VoCs for accurate detection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to enhancing statistical power, the inclusion of deletions as additional sites in the proposed pipeline (indicated by orange boxes in Supplementary Figure 2) played a significant role in the earlier detections of BA.2, BA.4, and BA.5 variants compared to Freyja. This advantage arises from the fact that no deletions were utilized in the inference process within the default settings of Freyja, a result previously discussed in another computational pipeline designed to analyze wastewater sequencing data 35 .…”
Section: Large-scale Genome Sequencing and The Development Of A Compu...mentioning
confidence: 99%
See 2 more Smart Citations
“…A multitude of studies have confirmed that SARS-CoV-2 can be detected in wastewater samples [5] and that we can estimate COVID-19 case numbers from such samples [33, 40, 41, 60]. Moreover, we can estimate the relative abundances of different SARS-CoV-2 lineages (and therefore different variants) from wastewater samples using amplicon-based sequencing [4, 15, 28, 30, 47, 48, 63], further emphasizing the applicability of amplicon-based sequencing. The key step in performing amplicon-based sequencing is designing a set of primers such that the genetic material of interest can be amplified [14].…”
Section: Introductionmentioning
confidence: 99%